Humoral responses against Trypanosoma brucei variable surface antigen are induced by degenerating parasites - Sendashoga, Cyrie N.; Black, Samuel J. (Wiley, 1982)
An analysis was made of the inductive stimuli for anti‐T. brucei variant surface glycoprotein (VSG) responses and the role played by humoral immunity in trypanosome wave control. The first wave parasitaemia was influenced by the rate of parasite differentiation from rapidly dividing slender forms to short lived stumpy forms. Remission of first wave parasitaemia was caused by a humoral immune response against external determinants of surface expressed VSG. Anti‐VSG responses were accompanied by anti‐trypanosome plasma membrane responses and were followed by non‐specific responses. Responses appeared to be initiated by fragments of parasites on which VSG external determinants and plasma membrane antigens were accessible and were possibly accelerated and amplified by a trypanosome mitogen which was not VSG. The parasite fragments may have arisen as a result of degeneration of stumpy form but not slender form parasites.